2010
DOI: 10.1038/clpt.2010.232
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Fluoroquinolone-Induced Elevation in Serum Creatinine Levels: A Case of Drug–Endogenous Substance Interaction Involving the Inhibition of Renal Secretion

Abstract: The aim of this study was to examine the mechanism underlying the elevation in serum creatinine levels caused by a novel des-fluoro(6)-quinolone antibacterial agent, DX-619, in healthy subjects. hOCT2 showed a prominent uptake of creatinine (K(m) = 56.4 mmol/l) among renal organic ion transporters. DX-619 is a potent inhibitor of hOCT2 (K(i) = 0.94 micromol/l), hMATE1 (0.82 µmol/l), and hMATE2-K (0.10 micromol/l). The pharmacokinetic model involving the inhibition of hOCT2 (model 1), hOCT2, and MATE1 or MATE2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 40 publications
3
91
2
Order By: Relevance
“…Recently, many researchers have focused on the mechanism of drug-induced hyperbilirubinemia (Zucker et al, 2001;Campbell et al, 2004;Chang et al, 2013;Wlcek et al, 2013;Chiou et al, 2014); however, the exact mechanism of drug-induced hyperbilirubinemia in humans and the relationship between the biomarkers and DDI from a quantitative perspective have not been elucidated. In other cases, previous studies have shown that when the renal transporters were inhibited by drugs, the plasma concentrations of creatinine, N-methylnicotinamide, and 6b-hydroxycortisol increased with the inhibition of OCT2 and/or MATEs, MATEs, and OAT3 by drugs, respectively (Imamura et al, 2011(Imamura et al, , 2014Ito et al, 2012). The utility of an endogenous substrate as a biomarker for transporter inhibition has been a topic of great interest.…”
Section: Biomarkers For Inhibition Of Transportersmentioning
confidence: 99%
“…Recently, many researchers have focused on the mechanism of drug-induced hyperbilirubinemia (Zucker et al, 2001;Campbell et al, 2004;Chang et al, 2013;Wlcek et al, 2013;Chiou et al, 2014); however, the exact mechanism of drug-induced hyperbilirubinemia in humans and the relationship between the biomarkers and DDI from a quantitative perspective have not been elucidated. In other cases, previous studies have shown that when the renal transporters were inhibited by drugs, the plasma concentrations of creatinine, N-methylnicotinamide, and 6b-hydroxycortisol increased with the inhibition of OCT2 and/or MATEs, MATEs, and OAT3 by drugs, respectively (Imamura et al, 2011(Imamura et al, , 2014Ito et al, 2012). The utility of an endogenous substrate as a biomarker for transporter inhibition has been a topic of great interest.…”
Section: Biomarkers For Inhibition Of Transportersmentioning
confidence: 99%
“…This focus on drug transporters promises to eventually improve understanding of pharmacokinetics in normal and diseased states (5). The endogenous metabolite, creatinine, is a well described substrate for OCT2 and apical MATEs; competitive inhibition of these carriers can cause increases in serum creatinine by blocking its excretion (Figure 2A) (29)(30)(31). Drugs such as cimetidine and trimethoprim are examples.…”
Section: Drugs and Toxinsmentioning
confidence: 99%
“…Similar to cisplatin, creatinine serves as an OCT2, MATE1, and MATE2K substrate (Urakami et al, 2004;Tanihara et al, 2007;Imamura et al, 2011;Ciarimboli et al, 2012); therefore, the possibility that vandetanib impacts creatinine clearance by inhibiting one or more of these transporters was also considered. Inhibition of transporters by vandetanib may influence the renal elimination and systemic exposure of certain transporter substrates, leading to drug-drug interactions (DDIs) and increased toxicity.…”
Section: Introductionmentioning
confidence: 99%